Online securities trading and control of securities offences in Malaysia - Jawahitha, , Sarabdeen; Mazahir, , Mohamed Ishak Mohamed (2006)
The paper addresses online securities trading and the possibility of occurrence of securities offences. Using online investment newsletters, bulletin boards, e-mail spam, etc online securities offences could be committed. Spreading false information about certain securities, non-disclosure of receiving commission for promoting stocks, practising false trading, market rigging, market manipulation are considered as fraud under the Malaysian legislation and whoever practices will be. prosecuted. The paper also analyses the available Malaysian, legal framework to control and curb the commission of securities related offences. The Securities Commissions Act 1993 provides regulatory framework for conduction e-trading activities while the Securities Industry Act 1983 makes. false trading, market rigging, market manipulation false and misleading information as regard to stocks as offences. The Contracts Act 1950 in section 18 allows the investors to recover damages and cancel. the trading of securities if the transaction was caused by misrepresentation. The Computer Crimes Act 1997 addresses threat like hacking cracking, transfer of classified and confidential information. The analysis of the legislation was done to see the adequacy of the existing laws to control the commission of securities offences. Beside the analysis of legislation and related cases the paper also analyses the provisions of guideline issued by the Malaysian Securities Commission to see the level of safeguard the Malaysian legal framework gives to the investors.